2017
DOI: 10.3847/1538-4357/aa8b77
|View full text |Cite
|
Sign up to set email alerts
|

Haro 11: Where is the Lyman Continuum Source?

Abstract: Identifying the mechanism by which high energy Lyman continuum (LyC) photons escaped from early galaxies is one of the most pressing questions in cosmic evolution. Haro 11 is the best known local LyC leaking galaxy, providing an important opportunity to test our understanding of LyC escape. The observed LyC emission in this galaxy presumably originates from one of the three bright, photoionizing knots known as A, B, and C. It is known that Knot C has strong Lyα emission, and Knot B hosts an unusually bright ul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 46 publications
4
65
0
1
Order By: Relevance
“…GW151226 [8] and GW170104 [9]-have shown that the early estimates for binary sources were, if anything, not optimistic enough. And shortly after the meeting, LIGO and the upgraded Virgo detector [10] announced not only a further binary black hole detection [11] but, most excitingly, the first detection of a binary neutron star merger [12], an event that was accompanied by a massive campaign of electromagnetic observations [13]. In view of these discoveries, we shall assess the promise of the very bright new era of gravitational-wave astronomy.…”
Section: A Long Roadmentioning
confidence: 95%
See 1 more Smart Citation
“…GW151226 [8] and GW170104 [9]-have shown that the early estimates for binary sources were, if anything, not optimistic enough. And shortly after the meeting, LIGO and the upgraded Virgo detector [10] announced not only a further binary black hole detection [11] but, most excitingly, the first detection of a binary neutron star merger [12], an event that was accompanied by a massive campaign of electromagnetic observations [13]. In view of these discoveries, we shall assess the promise of the very bright new era of gravitational-wave astronomy.…”
Section: A Long Roadmentioning
confidence: 95%
“…Over 70 different observing partners of LIGO and Virgo responded, locating the counterpart within half a day. The details of all this activity are reported in the first-ever gravitational-wave multi-messenger observation paper [13].…”
Section: Further Detectionsmentioning
confidence: 99%
“…High-resolution, spatially resolved spectroscopic data of some LyC leakers in the nearby Universe have been obtained recently to address this question (e.g. Keenan et al 2017;Micheva et al 2018;Menacho et al 2019). A comparably detailed theoretical investigation is demanded by these observations.…”
mentioning
confidence: 99%
“…比如在引力 波-电磁波对应体的一个清楚的物理联系就是双中 子星并合提供了引力波与电磁波的能量源. 与电磁 波宿主星系(例如文献 [90][91][92])已经有了很好的研究 不同, 目前仅仅观测到一个引力波源的宿主星系 [3] , 引力波宿主星系的更多性质将是未来更多引力波事 件被发现后, 在群族性质方向重要的课题(参见第4 节). 在这个观测大三角的图景下, 我们需要一个数 学方法来获取共同参数的信息以实现联合探测, 获 取其他有内秉联系的物理参数以探究二者之间物理 联系.…”
Section: 引力波简介unclassified